PENGARUH KEBUDAYAAN HUKUM (LEGAL CULTURE) DALAM KEHIDUPAN MASYARAKAT - LOILEWEN, ALINE FEBRIANY; TITAWATI, TITIN; ARDIKA, GEDE TUSAN; RAMLI, RAMLI; NOPIARI, IDA AYU (Ganec Swara, 2025)
This study aims to explain that law essentially grows and develops in society. Development carried out by the government in accordance with the plans and designs that have been prepared involves all aspects without exception. Of the many developments that must be carried out by the government, one of the segments is development in the legal field, which is related to other segments of life which is part of social symptoms. As is known, Indonesian society has a very diverse social and cultural structure, the problem that is often encountered in our society today is the legal culture that has not been running well. We often find good news from electronic media, print media, and online media about regional and central officials being caught red-handed because of bribery, corruption and so on. This is our common concern about what is happening in the government in our country. This study explains how the influence of legal culture in the lives of today's society, and how to build a good legal culture in society.